Geologia e mineralogia das rochas vulcânicas e hidrotermalizadas na região de Rincão da Cruzinha, Lavras do Sul, RS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The rocks of Lavras do Sul region have been studied since the discovery of potential economic deposits. Petrological and geochemical studies were carried out and verified the presence of volcanic, pyroclastic, plutonic and sedimentary rocks in a post-collisional Neoproterozoic environment which constitute the study area. Of these, plutonic and volcanic suffered hydrothermal alterations that allowed the placement of ore, or processes that allowed a greater enrichment of the mineralization. The study area is eastern to Lavras do Sul municipality in the locality known as Rincão da Cruzinha and comprises volcanic and pyroclastic rocks of the Hilário Formation. Field and drilling holes samples were collected and studied to characterize the mineralogy of whole rocks and also those with hydrothermal alteration. The descriptions of drill holes allowed to evaluate the compositional variation of the samples and to direct the microscopy’s studies. Thus, in the field, andesites, rhyolites and traquiandesites were defined, and, in general, in the holes tuffs with alteration characterized mainly by chloritization and hematitization, hydrothermal breccias, and vesiculated andesites, sometimes cut by carbonate veins were identified. Analysis at optical microscope with transmitted and reflected light as well as the studies in Scanning Electron Microscopy allowed the identification of the main minerals forming intermediate volcanic rocks and also of metallic and altering minerals. The main mineralogy of the andesites is composed of pyroxene, plagioclase, biotite and subordinately amphibole these rocks are widely distributed in the region mainly in massive form. However, vesicles filled by celadonite, quartz and chalcedony are locally observed. The rhyolites are composed of quartz, alkaline feldspar and biotite and, comprise fractured outcrops, aligned in the NW-SE direction. The traquiandesites are massive and composed of plagioclase microlites that denote trachytic texture, as well as pyroxenes and alkali feldspars. The tuffs are formed by microliths of plagioclase, biotite, pyroxene, chlorite and amphiboles besides hematite, ilmenite, apatite and titanite as accessories. Many tufts have ferric alteration (hematitization), which denotes reddish color in most of the rocks. The breccias have a light color and are composed of kaolinite, sericite and mainly, quartz and carbonate veins, as well as disseminated pyrite, galena, arsenopyrite and rutile. Of these metal minerals, the majority presents acicular form. Surface fault splines denote the proximity of the area’s rocks with a fault zone, which is reinforced by the presence of microfaults in the hydrothermal breccias. Considering the found mineralogy it can be said that the alteration occurring in the area is predominantly propylitic. In addition, rock geochemistry analysis revealed a large variation in the silica content of altered rocks from 30% to 67% and a standard behavior with a higher content of light REEs (43,78 ppm on average) than heavy REEs (1,62 ppm on average) in the analyzed rocks. The observed REE pattern meet the shoshonite affinity rocks that constitute ASLS.
Keywords: Rocha vulcânica; Alteração hidrotermal; Minerais metálicos; Volcanic rock; Hydrothermal alteration; Metallic minerals; CNPQ::CIENCIAS EXATAS E DA TERRA